2020
DOI: 10.1111/1462-2920.15307
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations inSynechococcusmicrodiversity in the Southern California coastal ecosystem

Abstract: Summary The Synechococcus cyanobacterial population at the Scripps Institution of Oceanography pier in La Jolla, CA, shows large increases in abundance, typically in the spring and summer followed, by rapid declines within weeks. Here we used amplicon sequencing of the ribosomal RNA internal transcribed spacer region to examine the microdiversity within this cyanobacterial genus during these blooms as well as further offshore in the Southern California coastal ecosystem (CCE). These analyses revealed numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
3
14
1
Order By: Relevance
“…During fall, Syn-223 (clade IV) commonly had a maximum relative abundance around 30 m while Syn-102 (clade I) was proportionally dominant below 50 m depth. This trend between the clades was not as clear in the summer, however, a similar pattern has been previously observed at multiple sites off the coast of southern California attributed to seasonal stratification ( Nagarkar et al, 2021 ). We observed that there was a greater degree of stratification below the shallow surface-mixing layer in fall compared to summer, but the deep-water mass showed similar stratification between the two seasons, only deeper by 5 m in September.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…During fall, Syn-223 (clade IV) commonly had a maximum relative abundance around 30 m while Syn-102 (clade I) was proportionally dominant below 50 m depth. This trend between the clades was not as clear in the summer, however, a similar pattern has been previously observed at multiple sites off the coast of southern California attributed to seasonal stratification ( Nagarkar et al, 2021 ). We observed that there was a greater degree of stratification below the shallow surface-mixing layer in fall compared to summer, but the deep-water mass showed similar stratification between the two seasons, only deeper by 5 m in September.…”
Section: Discussionsupporting
confidence: 80%
“…By August, Syn-223 (clade IV) slightly overcomes Syn-102 (clade I) in abundance. Similar patterns in clades IV and I dynamics have previously been observed in marine systems with clade I starting as the dominant clade during blooms and later shifting to IV ( Tai and Palenik, 2009 ; Nagarkar et al, 2021 ). This suggests there are either environmental factors that facilitate Syn-102 accumulation and dominance in early summer, which change to favor Syn-223 as the season progresses, or that Syn-102 is more of an opportunist and quickly responded to changes in the environment while Syn-223 more slowly grew to dominance.…”
Section: Discussionsupporting
confidence: 78%
“…Synechococcus cell abundance ranged from 10 3 to 10 4 cells/ml at the coastal stations ( Figure 2A ). It is lower than those in temperate or subtropic coastal waters, such as Bohai coastal marine ranch ( Li et al, 2021 ), Hong Kong coastal waters ( Liu et al, 2014 ), coastal western subtropical Pacific ( Tsai et al, 2006 ), and Southern California coast ( Nagarkar et al, 2021 ). However, it is consistent with those in other tropical coastal waters, such as the equatorial eastern Indian Ocean ( Wei et al, 2019 ) and coastal waters of the Philippines (Southeast China Sea) ( Agawin et al, 2003 ).…”
Section: Discussionmentioning
confidence: 96%
“…Marine Synechococcus exhibits high genetic diversity ( Farrant et al, 2016 ; Xia et al, 2019 ). Gene markers, such as the 16S rRNA gene ( Mackey et al, 2017 ), the 16S–23S internally transcribed spacer (ITS) ( Li et al, 2021 ; Nagarkar et al, 2021 ), the RNA polymerase gene ( rpo C1) ( Kent et al, 2019 ; Wang et al, 2021a ), the nitrate reductase gene ( nar B) ( Robidart et al, 2012 ), the cytochrome b 6 gene ( pet B) ( Mazard et al, 2012 ), and the ribulose–1,5–bisphosphate carboxylase oxygenase gene ( rbc L) ( Paerl et al, 2012 ), have been commonly applied to study the genetic diversity of Synechococcus . Among these gene markers, ITS is the locus with the most sequences available for primer design ( Ahlgren and Rocap, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, depth distribution might also be a relevant factor for interpreting the relative associations of Synechococcus clades with export. The mixed‐layer dominance of clades I and IV at all CCE sites is consistent with upwelling regions of the North and South Pacific (Zwirglmaier et al ., 2008; Sohm et al ., 2016; Nagarkar et al ., 2021). In the Sargasso Sea, however, clades II and III dominate the water column, with clade III more strongly associated with export (De Martini et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%